Adoption of Scientific Method of Cultivation of Rubber by Small Growers in Mavelikkara Taluk - Madavankutty Nair P G (Department of Plantation Crops and Spices, College of Horticulture, 1992)
An attempt was made to assess the rubber cultivation of Mavelikkara taluk of Alappuzha district. Primary data were collected through personal visits and interviews with the help of a questionnaire. Secondary data were gathered from the records available at the Field Offices of the Rubber Board. For the study, 100 units were chosen randomly from among those who planted rubber in 1985. Alappuzha district is comparatively new with respect to rubber cultivation. The region has the topography suited for rubber cultivation, with good soil and climatic features. Convertion of other crop areas to rubber was observed. There has been a tendency for raising higher number of plants per unit area than what is recommended, and only 14 per cent of the growers adopted the recommended planting distance. In majority of cases the pitting and refilling were found to be as per the recommended package of practices. Majority of the growers used advanced clones for planting. The most popular planting material had been RRII 105, which covered 92 per cent of the area under study. A general tendency for over manuring has been noticed. Intercropping was popular and some of the intercrops like betelvine were unique to this region, the feasibility of this needs further detailed studies. Cover cropping was not a regular practice in this area. There was atendency among the growers for opening the trees for tapping before attaining the recommended standard. As regards the exploitation system, out of 64 holders who started tapping, all except one followed ½ S d/2 system. The study revealed that growth of rubber is quite satisfactory in the area but indicated that the growers require more familiarization with the package of practices of the crop. Most of the growers were found not fully aware of the scientific cultivation practices for rubber. They were also found not availing the benefits of various extension schemes formulated by the Rubber Board and in short, more extension support is warranted in this line.